Mexican Lobby : Matías Romero in Washington 1861-1867 - Romero, Matías, 1837-1898 (Book collections on Project MUSE., 1986)
For Americans the Civil War was simply an internal conflict, and they have emphasized its military exploits and the romantic myths that have grown up around it. They have given little regard to its international aspects. In truth, however, the American Civil War attracted worldwide attention. Other nations followed the fortunes of the war and sought to understand its goals because they saw that the fate of the American system would likely have a profound effect on their own social and political economies.